JEAN-JACQUES ROUSSEAU : RÉFORMATEUR DE L’ÉCONOMIE POLITIQUE - Bienvenu, Métan Touré (European Scientific Journal, ESJ, 2015)
In this article, we show that Rousseau can still help us to rethink economics or economics at all. His economic thinking is an economy of abundance and sharing, based on moral values, such as non-envy. Agriculture is the foundation of its economic philosophy. If by that, our philosopher is close Physiocrats who are his contemporaries, they have not provided the same design concepts such as wealth, prosperity, abundance, making him both at political level that economically, a true revolutionary.